(untitled) (Research, Society and Development, 2022)
There has been a significant increase in new constructs involving the happiness and well-being of employees in companies and there are growing studies that prove that valuing employees is fundamental to the success of organizations, becoming a distinctive competitiveness factor. Furthermore, internal marketing is a recent approach that needs to be more intensified in organizations and implies approaching the employee as the first customer of an organization. It was carried out a case study of Organizational Happiness (FO) and Quality of Life at Work (QLW) in a jewelry industry, aiming to implement an Internal Marketing diagnosis. A questionnaire was constructed, integrating the scale of the Happiness Works project and items to measure QLW based on Walton, applied to a sample of 56 employees. As for the results: (a) moderate levels of FO were observed, tending to be happier in the Happiness in the Job dimension than in the Happiness in the Organization dimension; (b) the employees were not happy with the Remuneration and were quite happy with the Organization’s objectives; (c) the greater the number of children, the lower the satisfaction with remuneration; (d) the fewer qualifications they had, the lower the satisfaction with intrapreneurship and the job objectives; and (e) the higher the qualifications, the greater the satisfaction with the QLW. This paper ends with contributions to the company’s organizational development and approaches to promoting organizational happiness.